2010
DOI: 10.1530/eje-09-0901
|View full text |Cite
|
Sign up to set email alerts
|

Hypogonadism in females with Prader–Willi syndrome from infancy to adulthood: variable combinations of a primary gonadal defect and hypothalamic dysfunction

Abstract: Objective: The variable hypogonadism in Prader-Willi syndrome (PWS) has generally been attributed to hypothalamic dysfunction. Recent studies have documented primary testicular dysfunction in PWS males. Our aims were to characterize sexual development and reproductive hormones in PWS females and to investigate the etiology of hypogonadism. Design: A cross-sectional study. Methods: Physical examination was performed on 45 PWS females (aged 6 weeks to 32 years) and blood samples were obtained for hormonal analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 44 publications
2
46
1
Order By: Relevance
“…Consequently, plasma levels of estradiol were reduced by 35% in mir-7a2 KO female mice ( Figure 2F). Furthermore, as in male mice, gonadal fat pad weights were increased and dual energy x-ray absorptiometry (DEXA) measurements of fat and lean body mass revealed increased fat and decreased lean mass in 16-week-old mir-7a2 KO mice compared with WT littermate mice (Supplemental Figure 1, K-M), consistent with the hypogonadal-induced obesity observed in mice and humans (30,31). Together, these data illustrate that loss of mir-7a2, but not mir-7a1 or mir-7b, is sufficient to induce hypogonadism and infertility in mice.…”
Section: Introductionsupporting
confidence: 65%
“…Consequently, plasma levels of estradiol were reduced by 35% in mir-7a2 KO female mice ( Figure 2F). Furthermore, as in male mice, gonadal fat pad weights were increased and dual energy x-ray absorptiometry (DEXA) measurements of fat and lean body mass revealed increased fat and decreased lean mass in 16-week-old mir-7a2 KO mice compared with WT littermate mice (Supplemental Figure 1, K-M), consistent with the hypogonadal-induced obesity observed in mice and humans (30,31). Together, these data illustrate that loss of mir-7a2, but not mir-7a1 or mir-7b, is sufficient to induce hypogonadism and infertility in mice.…”
Section: Introductionsupporting
confidence: 65%
“…Although the hypogonadism in PWS has long been believed to be entirely hypothalamic, resulting in low gonadotropins and subsequent low gonadal hormones, recent studies have suggested that there is a combination of hypothalamic and primary gonadal deficiencies. [30][31][32] That conclusion was largely based on absence of hypogonadotropism and abnormally low inhibin B in both sexes. In a recent study, all 20 individuals with PWS who were evaluated had brain abnormalities that were not found in 21 sibs or 16 individuals with early-onset morbid obesity who did not have PWS.…”
Section: Other Endocrine Issuesmentioning
confidence: 99%
“…and a blood sample was taken for hormone assays. We previously reported hormonal data on 3 of the male infants and 1 of the female infants [11,17]. Written informed consent was obtained from the parents.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, the etiology of hypogonadism in PWS was attributed to hypothalamic dysfunction resulting in decreased secretion of gonadotropins from the pituitary [6,7]. However, we and others found that a primary defect in gonadal function is the major contributor to hypogonadism, especially in PWS adult men [8,9,10,11,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation